2012
DOI: 10.1002/jmv.23346
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of abnormal anal cytology in women infected with HIV

Abstract: Anal cancer is a rare disease. Nevertheless, it may be a reason for concern among groups in which its incidence is increasing: those who engage in anoreceptive intercourse, promiscuous persons, and those with sexually transmitted infections (HPV and HIV). The aim of this study was to evaluate the prevalence of abnormal anal cytology in women infected with HIV seen at Hospital de Clínicas de Porto Alegre, Brazil. A cross-sectional design was used. Anal smear screening was offered to all women infected with HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
2
16
2
Order By: Relevance
“…Current literature on the association between a history of receptive anal intercourse and abnormal anal cytology shows inconsistent results, 15,19,25,27 which might explain the discrepancy across population subsets in our study. Additionally, nearly half (40.8%) of the women in our study reported a history of receptive anal intercourse, comparable to reports from other studies on anal HPV and cytology among HIV-infected women in Brazil.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…Current literature on the association between a history of receptive anal intercourse and abnormal anal cytology shows inconsistent results, 15,19,25,27 which might explain the discrepancy across population subsets in our study. Additionally, nearly half (40.8%) of the women in our study reported a history of receptive anal intercourse, comparable to reports from other studies on anal HPV and cytology among HIV-infected women in Brazil.…”
Section: Discussioncontrasting
confidence: 70%
“…19,35 However, the literature documents an association between smoking and HSIL, while out study assessed potential risk factors for anal ASC-US + , which might explain the absence of a significant association in our study.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations